PENGARUH SOSIALISASI KEBIJAKAN COVID-19 TERHADAP KEPATUHAN MASYARAKAT MENERAPKAN PHYSICAL DISTANCING PADA PENGIKUT INSTAGRAM @LAWANCOVID19_ID - Riska Aura Ajib (2022)
This study aims to see how much influence socialization in the form of COVID19 information dissemination has on compliance with the application of physical distancing on the official government Instagram followers @lawancovid19_id by using the Edwards III implementation model theory by emphasizing the aspects of communication and disposition. The method used is correlational quantitative using primary data sources and secondary data. The sampling technique was done by simple random sampling. In this study, the analytical technique used is inferential statistics so that the research results can be generalized to the entire population. To analyze the results of the data used associative analysis which aims to see the impact of the independent variables on the dependent variable. The final result of this study shows that the effect of policy socialization on the implementation of physical distancing on Instagram followers lawancovid19_id is 28.4%. The hypothesis test shows a p-value < 0.05, proving that H0 is rejected and H1 is accepted. So it can be concluded that there is an Effect Of The Socialization Of Covid-19 Policy On Community Compliance Applying Physical Distancing On Instagram Followers @lawancovid19_id. Keywords: Policy Socialization, Physical Distancing Compliance, COVID-19, Edwards III Implementation Model